2000
DOI: 10.1515/cclm.2000.197
|View full text |Cite
|
Sign up to set email alerts
|

Serum Total and Lipid-Bound Sialic Acid Levels Following Acute Myocardial Infarction

Abstract: Although serum total sialic acid has been shown to be a cardiovascular risk factor, with elevated levels associated with increased cardiovascular mortality and also with cerebrovascular disease, the reason for the elevation in serum sialic acid content remains obscure. It has been shown that an increased output of serum proteins by the liver due to some type of acute phase reaction may be one of the possible sources of an increased serum sialic acid concentration in patients with myocardial infarction. An incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 26 publications
1
14
0
1
Order By: Relevance
“…It has been reported that SA concentration rapidly increases during the pathological circumstances since tissue destruction and proliferation ocur [17] . We propose that, in accordance with the reports published by other investigators previously [18] , these changes in SA levels originate from the over secretion of the lipid-bounded sialic acid compounds exerted by the sialoprotein synthesis in the liver [18] and increased sialidase enzyme activity [35] during the inflammation [36] .…”
Section: Discussionsupporting
confidence: 89%
“…It has been reported that SA concentration rapidly increases during the pathological circumstances since tissue destruction and proliferation ocur [17] . We propose that, in accordance with the reports published by other investigators previously [18] , these changes in SA levels originate from the over secretion of the lipid-bounded sialic acid compounds exerted by the sialoprotein synthesis in the liver [18] and increased sialidase enzyme activity [35] during the inflammation [36] .…”
Section: Discussionsupporting
confidence: 89%
“…22 An elevated concentration of serum total SA in the blood might result either from the shedding or secreting of SA from the cell membrane surface, or release of cellular SA from the cell into the bloodstream because of cell damage after myocardial injury. 4,7,23 It is known that a lot of ischemic changes occur during CABG, and the serum concentration of SA during CABG may contribute significantly to this ischemic process. In the samples taken from the artery and coronary sinus at 1 min after unclamping of aorta, early ischemic changes of CABG were seen.…”
Section: Circulation Journal Vol66 November 2002mentioning
confidence: 99%
“…Çeşit-li çalışmalarda tümör hücresinden veya miyokard hasarı sonrasında miyokard hücresinden dolaşıma sialik asidin salındığı bildirilmiştir (18,19). Hücre membranından SA kalıntılarının ayrılmasında, glikoprotein ve glikolipitlerden terminal SA kalıntılarının uzaklaştırılma-sını katalizleyen sialidaz rol oynar.…”
Section: Discussionunclassified